The Endurance and Contestations of Colonial Constructions of Race Among Malaysians and Singaporeans - Reddy, Geetha; Gleibs, Ilka H. (Frontiers in Psychology, 2019)
Psychological literature on race has discussed in depth how racial identities are dialogically constructed and context dependent. However, racial identity construction is often not compared across different socio-political contexts. By researching racial identity construction in three different multicultural countries, Malaysia, Singapore and the United Kingdom, we examined how three racial identities, Chinese, Malay and Indian, are constructed among Malaysians and Singaporeans in this qualitative study comprised of ten focus group discussions (N=39). We applied Dialogical Analysis to the data. This paper shows that both racial ingroups and outgroups constructed all three racial identities, with ingroups constructing their identities more heterogeneously compared to outgroups. Participants also engaged with colonial constructions of the three racial identities. The geographical locations, and therefore their perceptual contexts, of the participants differed. Yet, colonial constructions of race endured in contemporary identity construction and were contested in the group settings. We conclude that the socio-political context as understood by the context of colonialism and post-coloniality influenced their racial identity constructions. Participants, regardless of differences in geographical location, used similar colonial constructions of Malay, Chinese and Indian identities to position themselves as well as Others in their group interactions. These findings show that there is value in conceptualising the context beyond that which individuals are immediately presented with, and that psychologists should consider the inclusion of cultural legacies of colonialism in their conceptualisation of the present context.